Effect of surfactant on magnesium alloy with electroless Ni-P coating - Siti Rahmah Sarif, 1988-; Madzlan Aziz, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010